Transcutaneous auricular vagus nerve immediate stimulation treatment for treatment-resistant depression: A functional magnetic resonance imaging study - Ma, Yue; Wang, Zhi; He, Jiakai; Sun, Jifei; Guo, Chunlei; Du, Zhongming; Chen, Limei; Luo, Yi; Gao, Deqiang; Hong, Yang; Zhang, Lei; Liu, Yong; et al. (Frontiers in Neurology, 2022)
Objective Transcutaneous auricular vagus nerve stimulation (taVNS) is effective for treatment-resistant depression (TRD). In the current study, we observed the immediate modulating brain effect of taVNS in patients with TRD using rest-state functional magnetic resonance imaging (rs-fMRI). Method Forty patients with TRD and forty healthy controls (HCs) were recruited. Rs-fMRI was performed before and after 30 min of taVNS at baseline. The brain regions that presented significantly different the Regional Homogeneity (ReHo) between the TRD patients and HCs were selected as the ROI to calculate the functional connectivity (FC) of full brain. The correlations were estimated between the clinical scales' score and the functional brain changes. Results Following taVNS stimulation treatment, TRD patients showed significantly reduced ReHo in the medial orbital frontal cortex (mOFC) (F = 18.06, P < 0.0001), ANCOVA of the mOFC-Based FC images revealed a significant interaction effect on the left inferior parietal gyrus (IPG) and left superior marginal gyrus (SMG) (F = 11.6615, P<0.001,F = 16.7520, P<0.0001). Among these regions, the HAMD and HAMA scores and ReHo/FC changes were not correlated. Conclusion This study applied rs-fMRI technology to examine the effect of taVNS stimulation treatment on the brain activity of TRD. These results suggest that the brain response of TRD patients to taVNS treatment may be associated with the functional modulation of cortical regions including the medial orbital frontal cortex, the left inferior parietal gyrus, and the left superior marginal regions. Changes in these neuroimaging indices may represent the neural mechanisms underlying taVNS Immediate Stimulation treatment in TRD.